Endometriosis of the mesoappendix mimicking appendicitis: A case report - Suman Mewa Kinoo; Vikesh Ramkelawon; Bhugwan Singh (South African Medical Association, 2016)
Although appendicitis is largely a clinical diagnosis, on occasions diagnostic modalities may be needed to aid with the diagnosis. Despite the use of adjuncts and exploratory surgery, the diagnosis may not be clear until a histological diagnosis is achieved. Endometriosis of the appendix mimicking appendicitis is one of these diagnoses described in several case reports. Endometriosis of the meso-appendix has been described in association with intussusception of the appendix in several case reports. However, to our knowledge, endometriosis of the meso-appendix mimicking appendicitis has not been reported to date. We present the case of a 33-year-old woman with classic clinical signs and symptoms of appendicitis endorsed on computed tomography imaging. The patient underwent a laparoscopic appendicectomy with the postoperative histology demonstrating a normal appendix with endometriosis of the meso-appendix.